Determining treatment success in tubal ectopic pregnancies – the predictive value of the delta neutrophil index in single-dose methotrexate therapy - Korpe, Busra; Kose, Caner; Kucukbas, Gokce Naz; Celen, Sevki; Ustun, Yaprak Engin (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This study assessed the significance of the Delta neutrophil index (DNI) in predicting the effectiveness of single-dose methotrexate (MTX) treatment for tubal ectopic pregnancy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this retrospective study, 214 women diagnosed with tubal ectopic pregnancies and treated with MTX between 2019 and 2022 were included. Group 1 comprised 88 MTX responders, while group 2 consisted of 86 non-re sponders necessitating surgery. HCG and DNI levels were monitored on day 1, 4, and 7 of MTX treatment and compared be tween the groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Group 1 exhibited significantly lower HCG and DNI levels compared to group 2 on days 1, 4, and 7 (p<0.001). Both HCG and DNI levels on days 1 and 4 of MTX treatment were significant predictors of treatment failure, with the highest AUC observed for DNI was on day 4. In multivariate logistic regression analysis, elevated DNI levels on day 1 of MTX treatment were associated with a 5.8-fold increased risk, and DNI levels on day 4 were associated with a 4.44-fold increased risk of MTX treatment failure. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. DNI emerges as a valuable marker for predicting the success of single-dose methotrexate treatment in tubal ecto pic pregnancies, demonstrating superior predictive power compared to HCG.